HUBUNGAN KECANDUAN BERMAIN GAME ONLINE TERHADAP KUALITAS TIDUR DAN TEKANAN DARAH PADA MAHASISWA DI UPN VETERAN JAKARTA - Angga Bhakti Samudra (2023)
Online game is a video game using internet network. Addiction to playing online games can have a negative impact in various aspects, for example health, psychological, academic, social and financial. Sleep quality and blood pressure are examples of health aspects that can be affected by addiction to playing online games. The purpose of this study was to determine the relationship between online game addiction on sleep quality and blood pressure among students at UPN Veteran Jakarta. The research method used quantitative design with cross-sectional method and analyzed using the chi-square test. The sampling method was purposive sampling with 171 samples. Instruments in this study used the Internet Addiction Test (IAT), Pittsburgh Sleep Quality Index (PSQI) and blood pressure checks using a sphygmomanometer. Results showed the relationship between online game addiction and sleep quality with p-value of 0.000 (p<0.05). The relationship between online game addiction and blood pressure with p-value of 0.000 (p<0.05). It can be concluded that there is a significant relationship between addiction to playing online games on sleep quality and blood pressure. Researchers hope that online game players will maintain time so they get enough rest to maintain sleep quality and health to avoid the risk of hypertension.